Composite photocatalyst based on pyrite, preparation method and application in degradation of nitrogen-containing organic wastewater
By combining Nb2O5-x with pyrite, the composite material Nb2O5-x/FeS2 with Z-type heterojunction was prepared, which solved the problem of pyrite due to the limitation of oxide layer and low oxidation potential in photocatalysis, and achieved high efficiency It removes tetracycline hydrochloride from nitrogen-containing organic wastewater, and has high material stability, making it suitable for industrial applications.
Patent Information
- Application Number
- CN202411668074.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-21
AI Technical Summary
During the photocatalysis process, pyrite is limited by the oxide layer and low oxidation potential, and cannot effectively generate hydroxyl radicals (•OH), thereby hindering the effective progress of the photocatalytic reaction.
By combining with Nb2O5-x, a composite material Nb2O5-x/FeS2 with a Z-type heterojunction is prepared, and electrons are quickly transferred using the heterointerface to remove the oxide layer of pyrote, and the photocatalytic performance is improved.
It has achieved efficient removal of tetracycline hydrochloride in nitrogen-containing organic wastewater under visible light conditions, with a degradation rate of 89%. The material still maintains high photocatalytic activity after repeated use, showing good stability.
Smart Images

Figure CN119158597B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of visible light catalytic material research and environmental pollutant treatment technology, and in particular to a pyrite-based composite photocatalyst, a preparation method and an application in the degradation of nitrogen-containing organic wastewater. Background Art
[0002] Tetracycline is one of the antibiotics with the highest detection amount and detection rate in municipal organic wastewater. As a broad-spectrum antibiotic, tetracycline can remove most microorganisms and pathogens, and is the first choice for treating infections in clinical medicine and veterinary breeding. However, the abuse of tetracycline leads to the destruction of microbial ribosomes and the obstruction of protein synthesis, which reduces its effectiveness. Photocatalysis, as a strategy that can effectively remove antibiotics without causing secondary pollution, is one of the most direct and effective methods for treating organic pollutants. During the photocatalytic reaction, the photocatalyst generates electrons ( ) and holes ( ), which in turn generates active groups (·OH, ), these active substances can react with pollutants adsorbed on the surface of photocatalytic materials to effectively degrade the pollutants while avoiding secondary pollution.
[0003] Currently, the cost of synthesized composite photocatalysts in water treatment is very high, the yield is low and the product synthesis time is long. Natural semiconductor minerals can greatly reduce the treatment cost due to their low cost and easy access. Among them, pyrite (FeS2) has a suitable optical absorption potential, can produce active free radicals under photolysis, and exhibits strong redox activity. However, pyrite is hindered from being widely used in photocatalysis due to its inherent physical and chemical properties, including the formation of an oxide layer on the surface of pyrite and the inability to convert H2O / O2 into 2-H2O2 due to the low oxidation potential of the valence band (+0.42 eV). Oxidized to •OH (+2.38 eV), but unable to generate hydroxyl radicals (•OH). Since •OH is the main reactive oxygen species (ROSs) in the photocatalytic process; therefore, it is essential to modify pyrite with a suitable semiconductor. In view of this, the present invention provides a composite photocatalyst based on pyrite, a preparation method and an application in the degradation of nitrogen-containing organic wastewater. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a composite photocatalyst based on pyrite, a preparation method and an application of the degradation of nitrogen-containing organic wastewater, the purpose of which is to remove the pyrite oxide layer and convert Nb2O 5-x Preparation of Z-type heterojunction composite materials Nb2O with pyrite 5-x / FeS2, quickly transfer electrons through the heterogeneous interface to achieve efficient removal of nitrogen-containing organic wastewater.
[0005] The technical solution of the present invention to solve the above technical problems is as follows:
[0006] In the first aspect, a method for preparing a composite photocatalyst based on pyrite comprises the following steps: using pyrite and niobium oxalate as raw materials under melamine-assisted thermal activation conditions, and using a solvothermal method to prepare a pyrite composite material Nb2O having a Z-type heterojunction. 5-x / FeS2.
[0007] The principle is: the composite material Nb2O 5-x The migration path of / FeS2 follows the Z-type heterostructure, in which the photogenerated carriers separate rapidly under visible light response, generating and , which in turn generates active groups (·OH, ), these active groups can react with organic matter (such as tetracycline hydrochloride) adsorbed on the surface of the photocatalytic material, achieving efficient degradation of the organic matter.
[0008] The beneficial effects of the present invention are:
[0009] (1) The present invention prepares the composite material Nb2O by an in-situ growth method 5-x / FeS2, constructing a Z-type heterojunction of Nb2O 5-x / FeS2 composite materials can broaden the visible light response range of the material and promote the rapid separation of photogenerated carriers, thereby improving the photocatalytic performance of the material.
[0010] (2) The present invention modifies natural semiconductor pyrite, combines defect introduction and Z-type regulation strategy, and then uses an in-situ solvent thermal synthesis method. The operation is simple, the production cost is low, the synthesis purity is high, and the photocatalytic activity is still high after repeated use. It shows good stability and is suitable for large-scale engineering applications.
[0011] Based on the above technical solution, the present invention can also be improved as follows.
[0012] Furthermore, the pyrite is obtained by grinding natural pyrite and then sieving it through a 100-300 mesh sieve.
[0013] Furthermore, the mass ratio of the melamine to the pyrite is 0.03-0.05:0.4-1.0; the mass ratio of the niobium oxalate to the pyrite is 0.8-1.2:0.4-1.0.
[0014] The beneficial effect of adopting the above further scheme is that Nb2O with a high specific surface area and a surface defect structure is prepared by using the above amount. 5-x ; The oxide layer of pyrite was effectively stripped off through the solvothermal method, and a closely contacted heterostructure was constructed at the interface.
[0015] Furthermore, the pyrite composite material Nb2O 5-x Nb2O in FeS2 5-x It is a three-dimensional rod-shaped material containing oxygen defect structure.
[0016] Furthermore, the pyrite composite material Nb2O 5-x Nb2O in FeS2 5-x It is grown in situ on the layered structure of pyrite via a solvothermal method.
[0017] Further, the following specific steps are included:
[0018] (1) adding pyrite to a mixed solution of water and ethanol and mixing the mixture evenly, and adding niobium oxalate and melamine to obtain a mixture;
[0019] (2) subjecting the mixture to a solvent thermal reaction, filtering and drying after the reaction is completed, to obtain a pyrite composite material Nb2O having a Z-type heterojunction 5-x / FeS2.
[0020] Furthermore, in step (1), the mass volume ratio of the niobium oxalate to the mixed solution of water and ethanol is (0.8-1.2) g:20 mL; and the volume fraction of ethanol in the mixed solution of water and ethanol is 20%-35%.
[0021] The beneficial effect of adopting the above further scheme is that the present invention is more conducive to obtaining Nb2O by uniformly dispersing the solute in the solution and controlling the ratio of water and ethanol. 5-x Synthesis of tetragonal crystal system.
[0022] Furthermore, in step (2), the solvent thermal reaction is carried out by heating the temperature to 160°C-220°C and maintaining the constant temperature for 18h-24h, filtering, washing the filtered powder, and drying in an oven to obtain a pyrite composite material Nb2O with a Z-type heterojunction. 5-x / FeS2.
[0023] The beneficial effect of adopting the above further scheme is that a composite material with advantageous crystal faces and good crystallization is synthesized by a melamine-assisted thermal activation method.
[0024] Furthermore, in step (2), the drying is performed at 60° C. for 10 h to 12 h.
[0025] In a second aspect, a pyrite-based composite photocatalyst is prepared by the preparation method.
[0026] The third aspect is the application of the pyrite-based composite photocatalyst, which is used in the degradation of nitrogen-containing organic wastewater.
[0027] Furthermore, the pyrite-based composite photocatalyst is used in the degradation of tetracycline hydrochloride.
[0028] The beneficial effect of adopting the above further scheme is that under visible light conditions, the removal rate of tetracycline hydrochloride by the pyrite-based composite photocatalyst reaches 89%. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a comparison chart of X-ray powder diffraction of samples of the material to be tested in the present invention.
[0030] Figure 2 The composite material Nb2O 5-x / FeS2 high-resolution transmission electron microscopy; a) is FeS2 scanning electron microscopy, b) is Nb2O 5-x Scanning electron microscopy image, c) is 0.6Nb2O 5-x / FeS2 scanning electron microscope image, d) is 0.6Nb2O 5-x TEM image of / FeS2, ef) is 0.6Nb2O 5-x / FeS2HR TEM image.
[0031] Figure 3 It is the FT-IR spectrum diagram of the sample of the material to be tested of the present invention.
[0032] Figure 4 It is a comparison diagram of the ultraviolet-visible diffuse reflectance spectra of samples of the materials to be tested of the present invention.
[0033] Figure 5 This is a diagram of N2 adsorption desorption of a sample of the material to be tested in the present invention.
[0034] Figure 6 This is a diagram showing the photocatalytic degradation of tetracycline hydrochloride by a sample of the material to be tested according to the present invention.
[0035] Figure 7 It is a material cycle performance diagram of the material to be tested in the present invention.
[0036] Figure 8 A possible degradation pathway diagram for nitrogen-containing pollutants.
[0037] Fig. 9 This is a diagram of the photocatalytic mechanism of the composite material Nb2O5-x / FeS2 of the present invention. DETAILED DESCRIPTION
[0038] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased through regular channels.
[0039] Sources of materials and reagents:
[0040] In the following examples, FeS2 powder is obtained by grinding natural pyrite with a mortar, and the ground material is sieved through a sieve.
[0041] Example 1
[0042] This embodiment involves Nb2O 5-x The preparation of the / FeS2-1 composite comprises the following steps:
[0043] (1) Dissolve 1.076 g (2 mmol) of niobium oxalate reagent in a 60°C deionized water / ethanol mixed solution (the volume ratio of water / ethanol mixed solution is 3:1, and the amount is 60 mL), then add 45.6 mg (0.33 mmol) of melamine and stir evenly for 1 hour. Then weigh 0.4 g of FeS2 powder and add it to the above solution to form a mixed solution, and continue stirring for 10 minutes.
[0044] (2) The mixed solution was then transferred to a 100 mL polytetrafluoroethylene hydrothermal reactor, heated to 180°C, and maintained at a constant temperature for 22 h. After the reaction was completed and the reactor was cooled, the generated solid was collected by filtration, washed and filtered repeatedly with ethanol and deionized water, and dried in a 60°C oven for 12 h. Finally, the product was collected by filtration, washed several times with deionized water and ethanol, and then dried at 60°C for 12 h and collected, labeled as Nb2O 5-x / FeS2-1.
[0045] Example 2
[0046] This embodiment involves Nb2O 5-x The preparation of the FeS2-2 composite comprises the following steps:
[0047] (1) Dissolve 1.076 g (2 mmol) of niobium oxalate reagent in a 60°C deionized water / ethanol mixed solution (the volume ratio of water / ethanol mixed solution is 3:1, and the amount is 60 mL), then add 45.6 mg (0.33 mmol) of melamine and stir evenly for 1 hour. Then weigh 0.6 g of FeS2 powder and add it to the above solution to form a mixed solution, and continue stirring for 10 minutes.
[0048] (2) The mixed solution was then transferred to a 100 mL polytetrafluoroethylene hydrothermal reactor and heated to 180°C in two steps. The first step was to heat the reactor from room temperature to 120°C and maintain the temperature for 2 h. The second step was to heat the reactor from 120°C to 180°C and maintain the temperature for 22 h. After the reaction was completed and the reactor was cooled, the generated solid was collected by filtration, washed and filtered repeatedly with ethanol and deionized water, and dried in a 60°C oven for 12 h. It was labeled as Nb2O 5-x / FeS2-2.
[0049] Example 3
[0050] This embodiment involves Nb2O 5-x The preparation of the FeS2-3 composite comprises the following steps:
[0051] (1) Dissolve 1.076 g (2 mmol) of niobium oxalate reagent in a 60°C deionized water / ethanol mixed solution (the volume ratio of water / ethanol mixed solution is 3:1, and the amount is 60 mL), then add 45.6 mg (0.33 mmol) of melamine and stir evenly for 1 hour. Then weigh different masses of 0.8 g of FeS2 powder and add them to the above solution to form a mixed solution, and continue stirring for 10 minutes.
[0052] (2) The mixed solution was then transferred to a 100 mL polytetrafluoroethylene hydrothermal reactor and heated to 180°C in two steps. The first step was to heat the reactor from room temperature to 120°C and maintain the temperature for 2 h. The second step was to heat the reactor from 120°C to 180°C and maintain the temperature for 22 h. After the reaction was completed and the reactor was cooled, the generated solid was collected by filtration, washed and filtered repeatedly with ethanol and deionized water, and dried in a 60°C oven for 12 h. Finally, the product was collected by filtration, washed several times with deionized water and ethanol, and then dried at 60°C for 12 h and the product was collected and labeled as Nb2O 5-x / FeS2-3.
[0053] Example 4
[0054] This embodiment involves Nb2O 5-x The preparation of the FeS2-4 composite comprises the following steps:
[0055] (1) Dissolve 1.076 g (2 mmol) of niobium oxalate reagent in a 60°C deionized water / ethanol mixed solution (the volume ratio of water / ethanol mixed solution is 3:1, and the amount is 60 mL), then add 45.6 mg (0.33 mmol) of melamine and stir evenly for 1 hour. Then weigh 1.0 g of FeS2 powder of different weights and add it to the above solution to form a mixed solution, and continue stirring for 10 minutes.
[0056] (2) The mixed solution was then transferred to a 100 mL polytetrafluoroethylene hydrothermal reactor and heated to 180°C in two steps. The first step was to heat the reactor from room temperature to 120°C and maintain the temperature for 2 h. The second step was to heat the reactor from 120°C to 180°C and maintain the temperature for 22 h. After the reaction was completed and the reactor was cooled, the generated solid was collected by filtration, washed and filtered repeatedly with ethanol and deionized water, and dried in a 60°C oven for 12 h. Finally, the product was collected by filtration, washed several times with deionized water and ethanol, and then dried at 60°C for 12 h and the product was collected and labeled as Nb2O 5-x / FeS2-4.
[0057] Comparative Example 1
[0058] The preparation of the FeS2 sample of this comparative example comprises the following steps:
[0059] The FeS2 powder in this experiment was obtained from natural pyrite. The natural pyrite was ground in a mortar, and the ground material was sieved through a 200-mesh screen to obtain FeS2 powder.
[0060] Comparative Example 2
[0061] This comparative example Nb2O 5-x Sample preparation includes the following steps:
[0062] Dissolve 1.076 g of niobium oxalate reagent in a 60°C deionized water / ethanol mixed solution (the volume ratio of the water / ethanol mixed solution is 3:1, and the amount is 60 mL), then add 45.6 mg of melamine and stir evenly for 1 h. Then transfer the mixed solution to a 100 mL polytetrafluoroethylene hydrothermal reactor and heat it to 180°C twice. The first time, heat it from room temperature to 120°C and maintain it at a constant temperature for 2h, and the second time, heat it from 120°C to 180°C and maintain it at a constant temperature for 22 h. After the reaction is completed and the reactor is cooled, the generated solid is collected by suction, washed and filtered repeatedly with ethanol and deionized water, and dried in a 60°C oven for 12 h. The obtained solids are labeled as Nb2O 5-x .
[0063] Test example
[0064] 1. Detection method
[0065] For Nb2O in Examples 1-4 5-x / FeS2-1、Nb2O 5-x / FeS2-2、Nb2O 5-x / FeS2-3、Nb2O 5-x / FeS2-4 and FeS2, Nb2O in Comparative Example 1-2 5-x , perform the following tests:
[0066] (1) Structural characterization: X-ray powder diffraction, field emission scanning and transmission electron microscopy, Fourier transform infrared spectroscopy, and UV-visible diffuse reflectance spectroscopy.
[0067] (2) Photocatalytic degradation of organic wastewater and analysis of the composite materials.
[0068] Tetracycline hydrochloride was used as a model pollutant to evaluate the prepared photocatalytic material (Nb2O 5-x / FeS2-1,Nb2O 5-x / FeS2-2,Nb2O 5-x / FeS2-3,Nb2O 5-x / FeS2-4,FeS2,Nb2O 5-x ) degradation activity.
[0069] Specific process: 50 mg of photocatalytic material sample was added to tetracycline (100 mL, 20 mg / L) aqueous solution. The adsorption capacity and photocatalytic activity of the prepared photocatalytic material were studied in a glass apparatus equipped with a circulating cooling water system. A 300W xenon lamp and a cutoff filter (λ>400 nm) were used as the visible light source. Normally, magnetic stirring was performed for 30 min in dark conditions to achieve the adsorption-desorption equilibrium of tetracycline hydrochloride, and then the xenon light source was turned on for photocatalytic experiments. 3 ml of the suspension was taken every 15 min and the suspended matter was filtered through a nylon filter with a pore size of 0.22 μm. The absorbance of tetracycline was measured at the 275 nm absorption peak using a UV-visible spectrophotometer (UV-5100, METASH, Shanghai, PR China) and the degradation rate was calculated. The cuvette used was a quartz cuvette, and the absorbance value of water was zeroed before measuring the sample. The calculation formula for the degradation rate of tetracycline is:
[0070] 2. Test results
[0071] Figure 1 is a sample X-ray powder diffraction comparison diagram of the material to be tested in the present invention; Figure 1 It can be seen that the characteristic peaks at 22.7°, 26.6° and 46.5° correspond to the (101), (008) and (200) planes of Nb2O5, respectively, which are consistent with the diffraction pattern of the standard card of Nb2O5 (JCPDS 18-0911). Figure 1 The characteristic peaks of FeS2 at 28.5°, 33.0°, 37.0°, 40.7°, 47.3° and 56.2° correspond to the (111), (200), (210), (211), (220) and (311) crystal planes, respectively, which are consistent with the diffraction pattern of FeS2 (JCPDS 71-0053) standard material, indicating that the FeS2 in this experiment belongs to the cubic system. Composite material Nb2O5-x The characteristic peaks of FeS2 and Nb2O5 coexist in the XRD spectrum of / FeS2, indicating that the composite material Nb2O 5-x Nb2O in FeS2 5-x The crystal structure of FeS2 and Nb2O remains intact. In addition, the intensity of the characteristic peak of FeS2 gradually weakens with the decrease of its content in the material, but it still shows obvious characteristic peaks, indicating that the introduction of Nb2O 5-x The crystal structure of FeS2 is not affected.
[0072] Figure 2 The composite material Nb2O 5-x / FeS2 high-resolution transmission electron microscopy images, where a) is FeS2 scanning electron microscopy image, b) is Nb2O 5-x Scanning electron microscopy image, c) is 0.6Nb2O 5-x / FeS2 scanning electron microscope image, d) is 0.6Nb2O 5-x / FeS2TEM image, ef) is 0.6Nb2O 5-x / FeS2HR TEM image. Figure 1 X-ray powder diffraction pattern and Figure 2 From the transmission electron microscopy image, we can see that the crystal plane distances of 0.402 nm and 0.312 nm correspond to the (101) plane of Nb2O5 and the (111) plane of FeS2, indicating that the main crystal plane of synthesized Nb2O5 is the (101) plane, while Nb2O 5-x Growing towards the (101) plane. Nb2O 5-x Tightly grown on the FeS2 layer, a compact composite material was constructed.
[0073] Figure 3 The FT-IR spectrum of the sample of the material to be tested in the present invention is shown in Figure 5. -1 The overlapping broad peaks may be related to the stretching vibrations of Nb-O and Nb=O. -1 and 1679 cm -1 The peak at 1400 cm-1 is attributed to the C=O stretching vibration of the carboxyl group. -1 The peak at 1260 cm-1 is derived from the symmetric stretching vibration of C=O and CO. -1 The weak peak at 418 cm -1 The absorption peak at is attributed to the stretching vibration of Fe-S bond.
[0074] Figure 4 The UV-visible diffuse reflectance spectra of the samples of the materials to be tested in the present invention are compared. 5-xThe light absorption edge is 425 nm. 5-x / FeS2, with the increase of FeS2 content in the component, the red shift amplitude becomes larger and larger, showing a stronger response ability to visible light.
[0075] Figure 5 The N2 adsorption and desorption diagram of the sample of the material to be tested in the present invention is shown in FIG. 5-x There is an obvious H1 type hysteresis loop in the range of greater than 0.4, and the pore size distribution is mainly concentrated in 10-40 nm, which is a typical mesoporous material. FeS2 has an obvious H3 type hysteresis loop in the range of greater than 0.2, indicating that the pore structure of FeS2 is mainly composed of large pores. Combined with the specific surface area and pore volume data of FeS2 in the table, it shows that the surface of FeS2 is smooth, the layered particles are stacked to form holes, and the adsorption capacity of N2 is extremely low. Nb2O 5-x / FeS2 composite material also shows obvious H1 type hysteresis loop in the range of greater than 0.4, and the pore size is mainly distributed in 10-20 nm, indicating that the Nb2O 5-x / FeS2 material is a mesoporous material. 5-x The adsorption-desorption curve and pore size distribution of / FeS-2 are better than those of other composite materials. 5-x The specific surface area and pore volume data of FeS2 show that Nb2O 5-x The / FeS2 composite material has a large-pore-mesoporous structure because Nb2O5 is attached to the surface of pyrite and forms a macroporous-mesoporous structure in the macropores formed by the stacking of FeS2 flake particles, which increases the specific surface area of FeS2. In addition, as the FeS2 content in the composite material increases, the specific surface area and pore volume of the composite material begin to decrease, but are better than pure FeS2, indicating that the introduction of FeS2 provides more adsorption sites for pyrite, increases the reaction area, and enhances the photocatalytic efficiency.
[0076] Figure 6 This is a photocatalytic degradation effect diagram of tetracycline hydrochloride of a sample of the material to be tested in the present invention. Figure 6 As shown, under simulated sunlight conditions, Nb2O 5-x / FeS2-2 photocatalyst has stronger photocatalytic degradation performance, and the degradation rate of tetracycline hydrochloride can reach 89% under 60 minutes of illumination.
[0077] Figure 7 The material cycle performance diagram of the material to be tested in the present invention. After 5 cycle experiments, the final removal rate of tetracycline by Nb2O5 / FeS2-2 decreased from 88.19% to 80.50%, and the removal rate of tetracycline was still above 80%, indicating that Nb2O5 / FeS2-2 has high photodegradation efficiency and good stability under visible light.
[0078] Figure 8 The following is a possible degradation pathway diagram of nitrogen-containing pollutants. For pathway I, due to the action of ·OH, tetracycline undergoes multiple hydroxylations and dehydration to be broken into TC5 (m / z=459), after which TC1 is deamidated to form TC6 (m / z=400), followed by the reduction of the methyl and amino groups of TC2 to form TC7 (m / z=343), and finally decarbonization to form TC8 (m / z=301). Pathway II is because tetracycline undergoes demethylation and hydroxylation to form TC1 (m / z=435), after which the intermediate is converted into TC2 (m / z=415) under further deamination and methylation reactions, followed by ring-opening degradation to TC3 (m / z=318), and finally deamidation to form TC4 (m / z=274). Pathway III is that the methyl group of tetracycline is destroyed to generate TC9 (m / z=403), which is degraded to generate TC10 (m / z=337) through a series of reactions such as deamidation, deamination, hydroxylation, carbonylation, addition reaction and ring-opening reaction. However, the enol structure in TC10 is unstable and will be converted into keto form to form TC11 (m / z=337). Finally, the final products under the three pathways are generated through a series of oxidation reactions to generate TC12 (m / z=196), TC13 (m / z=149), TC14 (m / z=127), and TC15 (m / z=117).
[0079] Fig. 9 The composite material Nb2O 5-x / FeS2 photocatalytic mechanism diagram. The improvement in photocatalytic performance is mainly attributed to the rapid separation of photogenerated carriers. 5-x / The migration path in FeS2 follows Fig. 9 The Z-shaped heterostructure shown. The composite material is generated in response to visible light. and , which in turn generates active groups (·OH, ), these active substances can react with tetracycline hydrochloride adsorbed on the surface of the photocatalytic material. 5-x / FeS2 has strong redox ability and achieves efficient degradation of tetracycline hydrochloride.
[0080] In summary, the present invention prepares Nb2O by in-situ growth method. 5-x / FeS2, fully exposed active sites, achieve maximum response to visible light, and construct a Z-type heterojunction of Nb2O 5-x / FeS2 composite material, broadens the visible light response range of the material, promotes the rapid separation of photogenerated carriers, and thus improves the photocatalytic performance of the material. The present invention modifies the natural semiconductor pyrite powder, combines defect introduction and Z-type regulation strategy, and combines in-situ hydrothermal synthesis. It is simple to operate, low in production cost, and high in synthesis purity. At the same time, it shows that it still maintains high photocatalytic activity after repeated use, showing good stability, and is suitable for expanding chemical industry applications.
[0081] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a composite photocatalyst based on pyrite, characterized in that: The preparation method comprises the following steps: (1) adding pyrite to a mixed solution of water and ethanol and mixing the mixture evenly, and adding niobium oxalate and melamine to obtain a mixture; (2) subjecting the mixture to a solvent thermal reaction, filtering after the reaction is completed, and drying to obtain a pyrite composite material Nb2O3 having a Z-type heterojunction 5-x / FeS2, which is the pyrite-based composite photocatalyst; The solvent thermal reaction is carried out by heating the temperature to 160°C-220°C and maintaining the constant temperature for 18h-24h; The pyrite is obtained by grinding natural pyrite and sieving it through a 100-300 mesh sieve; The mass ratio of melamine to pyrite is (0.03-0.05): (0.4-1.0); the mass ratio of niobium oxalate to pyrite is (0.8-1.2): (0.4-1.0); The pyrite composite material Nb2O 5-x Nb2O in FeS2 5-x It is grown in situ on the layered structure of pyrite by solvothermal method; The pyrite composite material Nb2O 5-x Nb2O in FeS2 5-x It is a three-dimensional rod-shaped material containing oxygen defect structure.
2. The method for preparing the composite photocatalyst based on pyrite according to claim 1, characterized in that: In step (1), the mass volume ratio of the niobium oxalate to the mixed solution of water and ethanol is (0.8-1.2) g:20 mL; and the volume fraction of ethanol in the mixed solution of water and ethanol is 20%-35%.
3. A composite photocatalyst based on pyrite, characterized in that: Prepared by the preparation method according to any one of claims 1 to 2.
4. Application of composite photocatalyst based on pyrite, characterized in that: The pyrite-based composite photocatalyst described in claim 3 is used in the degradation of nitrogen-containing organic wastewater.
Citation Information
Patent Citations
Niobic acid-based sulfide composite material and preparation method thereof
CN110586133A
Catalyst for hydrogen production through photocatalytic decomposition of water and preparation method thereof
CN116550338A